The Integrated Hydropower Sustainability Assessment in Tajikistan: A Case Study of Rogun Hydropower Plant. (10th September 2020) - Xu, Zhao; Niu, Yumin; Liang, Yangze; Li, Zhigang; Iftikhor, Atoev
Abstract : Tajikistan has formulated the strategy to rejuvenate the country through hydropower. The Rogun hydropower plant (HPP) is designed as the highest hydropower station, while its sustainability is also questioned due to a lack of comprehensive sustainability evaluation. Considering that the external environment of Rogun HPP is complex and changeable, its sustainable performance will be fragile and inconstant. To comprehensively assess the sustainable performance, an integrated evaluation framework, covering the current and dynamic sustainable performance, is urgently established. Therefore, this paper firstly explored the hydropower sustainability assessment indicators which can conform to Tajikistan's situations and further examined the current sustainable performance of Rogun HPP. The case study found that Rogun HPP's current financial viability, involuntary resettlement, the measures to prevent corruption, and information disclosure were seriously deficient. The SWOT analysis indicated the external factors, such as the Belt and Road Initiative, improving business environment, and easing geopolitical disputes, can eliminate weaknesses and improve the sustainable performance of Rogun HPP. At the same time, tight fiscal allocations and economic downturns will have negative influences on the sustainable performance. The integrated evaluation tool established in this paper can not only evaluate the current sustainable performance but also consider the impact of external factors on sustainable performance from a dynamic perspective. This paper contributes to the current knowledge system by establishing the hydropower sustainability assessment system which is suitable for Tajikistan's conditions. Moreover, the results are informative for the decision-makers to have a better understanding of Rogun HPP's current strengths and weaknesses, valuable opportunities, and potential threats.